Role of national media in educating children aged 8 to 12 Case study: 8-12 year old boys and girls from District 7 of Tehran Education - Ghavimi, Fatemeh (International Journal of Psychosocial Rehabilitation, 2020)
The media is certainly an integral part of the lives of today’s people, children and adolescents, who are in fact the main audience of the media. The processing power and accurate analysis of information and news received is lower in children than in adults. On the other hand, centralized monitoring to control the media outputs is becoming increasingly problematic. Therefore, the awareness of the audience, parents, teachers and professors about media literacy can guide us towards the consequences of these media. This research is a case study that deals with the role of national media in educating children (male and female students aged 8-12) from District 7 of Education in Tehran Province.Research Methods: In this field and library research, we have used descriptive statistics (mean, mean, variance and standard deviation) and inferential statistics (t-test and logistic regression) to analyze the data. We have used the researcher-made questionnaire tool to investigate the research hypotheses. Conclusion: Examining the results of the Chi-Square test, the Kalmogrov-Smirnov test, the calculation of skewness and kurtosis, we examined the hypotheses and concluded that: "Direct education from the national media is effective in learning", "Education is associated with the national media", "the national media have a special place as an informal learning tool." These results are in complete agreement with the results of other similar studies.